2022
DOI: 10.1016/j.jbc.2021.101441
|View full text |Cite
|
Sign up to set email alerts
|

A highly conserved zebrafish IMPDH retinal isoform produces the majority of guanine and forms dynamic protein filaments in photoreceptor cells

Abstract: Inosine monophosphate dehydrogenase (IMPDH) is a key regulatory enzyme in the de novo synthesis of the purine base guanine. Dominant mutations in human IMPDH1 cause photoreceptor degeneration for reasons that are unknown. Here, we sought to provide some foundational information on Impdh1a in the zebrafish retina. We found that in zebrafish, gene subfunctionalization due to ancestral duplication resulted in a predominant retinal variant expressed exclusively in rod and cone photoreceptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
(107 reference statements)
1
4
0
Order By: Relevance
“…In retinal cells, the presence of cytoophidium is tightly regulated by light conditions, as demonstrated in previous studies ( Plana-Bonamaiso et al, 2020 ; Cleghorn et al, 2022 ). This regulation is of particular significance in photoreceptor cells where IMPDH1 is highly overexpressed.…”
Section: Discussionsupporting
confidence: 74%
“…In retinal cells, the presence of cytoophidium is tightly regulated by light conditions, as demonstrated in previous studies ( Plana-Bonamaiso et al, 2020 ; Cleghorn et al, 2022 ). This regulation is of particular significance in photoreceptor cells where IMPDH1 is highly overexpressed.…”
Section: Discussionsupporting
confidence: 74%
“…We recently characterized IMPDH1 filaments in the zebrafish retina, finding a circadian pattern to filament assembly, with elongated filaments forming in photoreceptors during the day and smaller punctate structures at night (Cleghorn et al, 2022). We also showed that the zebrafish IMPDH1 retinal variants are very similar to human IMPDH1 in terms of structure, filament assembly, and regulation (Cleghorn et al, 2022). This is consistent with our finding here that the S477D mutation, which mimics dark-dependent phosphorylation, disrupts filament assembly and reduces enzyme activity in the presence of GTP.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human IMPDH1 retinal variant proteins were expressed and purified as described previously (Anthony et al, 2017; Burrell et al, 2022; Cleghorn et al, 2022). Briefly, BL21 (DE3) E. coli cells were transformed with wildtype or S477D mutant IMPDH1(546) or IMPDH1(595) expression vectors.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclic GMP is the key signaling molecule in the phototransduction cascade [62][63][64] while photoreceptors have an exceptionally high demand for ATP [65]. On top of this, there is a lack of redundancy in purine nucleotide production as there is very little expression of both IMPDH2 [53,66] and the major purine salvage enzyme HPRT [67,68]. Imbalanced purine pools in photoreceptors can lead to cell death [69,70].…”
Section: Impdh1-associated Retinitis Pigmentosamentioning
confidence: 99%
“…Treatment of IMPDH1-associated RP poses a unique challenge not only because it is autosomal dominant but also because there are only low levels of expression of the other isoform [ 53 , 66 ] in the retina to maintain purine biosynthesis. Therapeutic delivery to the retina is most commonly achieved by intravitreal injection.…”
Section: Introductionmentioning
confidence: 99%